ANALISIS PERATURAN STRATEGI PENGGUNAAN ENERGI TERBARUKAN DI INDONESIA: SEBUAH TINJAUAN - Ester Nugraheny Natalia Purba; Chairul G. Irianto (G-Tech: Jurnal Teknologi Terapan, 2025)
This article discusses developments in the use of renewable energy in Indonesia, identifies the obstacles faced, and offers innovative solutions for managing renewable energy in this country. The aim of the research is to increase awareness of researchers, policy makers and investors about Indonesia's great potential in the field of renewable energy, as well as increasing capabilities in its use. This research seeks to provide new insights to policy makers for future decision making, in achieving the target of renewable energy use of up to 31% by 2050 in accordance with the General National Energy Plan (RUEN). This research uses a qualitative descriptive method to analyze conditions for the use of renewable energy, readiness, obstacles, and solutions that support the achievement of RUEN goals. By referring to the latest scientific literature, government poli-cies, and regulations, this article seeks to explain the relationship between renewable energy sources, energy policies, and relevant strategies to advance the use of renewable energy in Indonesia. The findings indicate that the government faces a significant challenge in aligning the energy mix target by 2050 with the current realization. Insufficient regulations and lack of research and development of renewable energy technology may also contribute to this challenge.